2018
DOI: 10.1051/0004-6361/201833506
|View full text |Cite
|
Sign up to set email alerts
|

Physics of the Applegate mechanism: Eclipsing time variations from magnetic activity

Abstract: Since its proposal in 1992, the Applegate mechanism has been discussed as a potential intrinsical mechanism to explain transit timing variations in various kinds of close binary systems. Most analytical arguments presented so far focused on the energetic feasibility of the mechanism, while applying rather crude one-or two-zone prescriptions to describe the exchange of angular momentum within the star. In this paper, we present the most detailed approach to date to describe the physics giving rise to the modula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 33 publications
(89 reference statements)
2
42
0
Order By: Relevance
“…Refinements where later brought by Brinkworth et al (2006) who introduced a treatment based on a finite shell and a core, followed by Völschow et al (2016) who generalised that approach to more realistic density profiles of the companion star. Alternatively, Lanza (2005Lanza ( , 2006 introduced a treatment of the complete continuous redistribution of angular momentum across the entire convective zone of the star, later expanded by Völschow et al (2018). In all these models, the underlying magnetic cycle are imposed as ad hoc assumptions.…”
Section: The Phase-locked Quadrupole Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Refinements where later brought by Brinkworth et al (2006) who introduced a treatment based on a finite shell and a core, followed by Völschow et al (2016) who generalised that approach to more realistic density profiles of the companion star. Alternatively, Lanza (2005Lanza ( , 2006 introduced a treatment of the complete continuous redistribution of angular momentum across the entire convective zone of the star, later expanded by Völschow et al (2018). In all these models, the underlying magnetic cycle are imposed as ad hoc assumptions.…”
Section: The Phase-locked Quadrupole Potentialmentioning
confidence: 99%
“…However qualitatively successful, this simulation is restricted in range and cannot assess fully realistic cases due to the overwhelming computing power needed. Most of the aforementioned models (in particular Lanza (2006); Völschow et al (2016Völschow et al ( , 2018; Navarrete, Schleicher, Käpylä, Schober, Völschow & Mennickent (Navarrete et al)) conclude that it is impossible to produce the observed magnitude of orbital period variations with the Applegate mechanism only, except maybe for postcommon-envelope systems with companions slightly below the fully-convective mass limit m c ∼ 0.35M (Lanza 2006;Völschow et al 2018). Interestingly, these might be akin to redback companions.…”
Section: The Phase-locked Quadrupole Potentialmentioning
confidence: 99%
“…by stellar magnetic cycles as proposed in Applegate (1992) and later refined by e.g. Lanza & Rodonò (1999); Lanza (2006); Völschow et al (2018);Navarrete et al (2019). If quadrupole-moment changes are responsible for the observed orbital period variations, then it is possible to design a dynamical model of the binary that includes this contribution.…”
Section: Introductionmentioning
confidence: 96%
“…In addition to the finite shell model, Lanza & Rodonò (2004) and Lanza (2005) presented a one-dimensional framework based on the angular momentum transport equations, using simplifying assumptions of magneto-hydrodynamical (MHD) turbulence and the mean magnetic field. We have extended this framework in Völschow et al (2018), considering in particular time-dependent hydrodynamic and magnetic fluctuations assuming a magnetic activity cycle, as well as a superposition of different modes. For typical RS Canum Venaticorum (RS CVn) systems, which are detached binaries typically composed of a chromospherically active G or K star, the expected eclipsing time variations are however two orders of magnitude lower than observed.…”
Section: Introductionmentioning
confidence: 99%
“…For typical RS Canum Venaticorum (RS CVn) systems, which are detached binaries typically composed of a chromospherically active G or K star, the expected eclipsing time variations are however two orders of magnitude lower than observed. The most promising Applegate candidates are post-common-envelope binaries with secondary masses of ∼ 0.35 M (Völschow et al 2018), as these produce more energy through nuclear burning and can thus more easily redistribute angular momentum as required by the Applegate mechanism, while simultaneously not being critically affected by the presence of a radiative core.…”
Section: Introductionmentioning
confidence: 99%